Lifestyle of Hormoz Island Residents: A Cross-Sectional Study - Teamur Aghamolaei; Sayed Hossein Davoodi; Abdoulhossain. Madani; Ali Safari-Moradabadi; Sakineh Dadipoor (Hamadan University of Medical Sciences, 2018)
Background and Objective: Lifestyle-related diseases are among the most important causes of mortality in Iran. Evidence suggests an association between unhealthy lifestyle and the incidence of diseases and health problems. Therefore, the present study was conducted to determine the status of lifestyle and its related factors among the residents of Hormoz Island, Iran. Materials and Methods: This cross-sectional study was conducted on 400 inhabitants of Hormoz island with the age of over 15 years in 2016. The study population was selected by two-stage cluster sampling method. The demographic information and data related to life-style were collected through a researcher-made questionnaire, confirmed to be reliable and valid. Data analysis was performed in SPSS (version 19) using descriptive statistics, Chi-square test, and one-way ANOVA. Results: According to the results, the mean age of the participants was 36.1±14.52 years. In terms of lifestyle, the consumption of liquid oil, low-salt food, regular physical activity, and non-smoking had the frequencies of 81%, 20.3%, 37%, and 68.3%, respectively. Furthermore, the mean consumptions of fruits, vegetables, and fish were 2.48, 3.55, and 3.65 food units per week, respectively. Additionally, there was a significant relationship between education level and salt consumption (P=0.002), economic status and type of consumed oil (P<0.005), as well as healthy diet pattern and economic status of individuals (P<0.05). Conclusion: As the findings indicated, the promotion of nutritional knowledge, increased awareness of the disadvantages of smoking in people with low education, implementation of cheap policies, availability of healthy food, increased tobacco taxes, implementation of physical activities, as well as notification and normalization in the field of safety behaviors are among the important factors for the promotion of lifestyle.